Relationship-Courier Partner Logistics and E-Commerce Enterprises in Malaysia: A Review - Nurul, Izzah; Damhuji, Rifai; Liu, Yao (Informatics Publishing Limited, 2016)
Background/Objectives: The term “logistics services and e-commerce” have been in use for more than 10 years, but has recently become an important subject of analysis and empirical investigation. It is common in Malaysia in logistics services like courier services companies which they call customers for whom buy their services and for e-commerce enterprises that they call courier services companies as a business partner or Courier Partner Logistics (CPL) where CPL provided any logistics services for their business operations. This paper presents and reviews the milestone and development of logistics operations in courier services companies and e-commerce enterprises in Malaysia. This paper also will show the relationship between both of them which are logistics/courier services companies and e-commerce enterprises. Methods/Analysis: We use a qualitative and quantitative method such as interview and observation (qualitative) to verify of questionnaires (quantitative) this study by experts in the field of logistics especially in courier firms and e-commerce enterprises. Findings: In reviewing literature we find that online users in Malaysia are greater than Singapore, but for Malaysia’s e-commerce of retail only 0.2% compared than Singapore 1.0%. It means entrepreneurs in Malaysia still not aware in utilization and advantages of Internet or ICT in their business. In Asian countries, most of among them are still in initial stage to the development of e-business, especially Malaysia, but for e-commerce level companies Malaysia, they also try to show good performances and advanced with assistance and support by Malaysia government such as Multimedia Development Corporation (MDeC) and efficiency of logistics by courier companies within product delivery service provider, so this is one way to e-commerce enterprises develop business towards to e-business level. Applications: In conclusion, it could help to acknowledge the current levels management and ability as well as the role of logistics/courier services and e-commerce enterprises’ performances. Thus, it could guide both of them to renew their perceptions of the effects of the managing knowledge operations and services to better develop and also enhance their operational practices. So, both of them could survive their business to compete with others competitors. In addition, the significance of this study and benefit for future research is clearly known about the relationship strength between them (relationship among the two industries namely courier services companies and e-commerce enterprises’ performances).